The Analysis of Performance of State Civil Apparatus at The Regional Financial and Assets Management Agency of Supiori District - Hermanu Iriawan; Diah Novita Sari; Samsiah Samsiah (PINISI Discretion Review, 2021)
In facing the era of globalization which is full of challenges and opportunities, state apparatus as public servants who provide the best service towards good governance. This study uses a qualitative approach. With observation data collection techniques and in-depth interviews. This study aims to analyze the performance of the State Civil Apparatus at the Regional Financial and Asset Management Agency of Supiori Regency. This study aims to determine and analyze the performance of the State Civil Apparatus at the Regional Financial and Asset Management Agency of Supiori Regency and to identify and analyze the supporting and inhibiting factors of the performance of the State Civil Apparatus at the Regional Financial and Asset Management Agency of Supiori Regency. The results showed that the performance of financial and asset managers in the Supiori district was still in the "medium" category, tending to be "low". This means that there is a need for internal organizational policies to improve employee performance and the factors that affect the performance of financial and asset managers in Supirori Regency, seen from their human resources, are still varied and categorized as low. What is owned is not in accordance with the tupoksi owned, judging from the competence of work from the aspect of formal education, it seems that it is not very important in encouraging the improvement of the performance of the apparatus, while the aspects of education and training and work experience play an important role in encouraging the improvement of employee performance.